For home and country : World War I propaganda on the home front - Kingsbury, Celia Malone (Lincoln : University of Nebraska Press, 2010)
World War I prompted the first massive organized propaganda campaign of the twentieth century. Posters, pamphlets, and other media spread fear about the "Hun", who was often depicted threatening American families in their homes, while additional campaigns encouraged Americans and their allies to support the war effort. With most men actively involved in warfare, women and children became a special focus and a tool of social manipulation during the war. This work examines the propaganda that targeted noncombatants on the home front in the United States and Europe during World War I. Cookbooks, popular magazines, romance novels, and government food agencies targeted women in their homes, especially their kitchens, pressuring them to change their domestic habits. Children were also taught to fear the enemy and support the war through propaganda in the form of toys, games, and books. And when women and children were not the recipients of propaganda, they were often used in propaganda to target men. By examining a diverse collection of literary texts, songs, posters, and toys, the author reveals how these pervasive materials were used to fight the war's cultural battle.
Introduction -- Food will win the war : domestic science and the royal society -- "One hundred percent" : war service and women's fiction -- VADs and khaki girls : the ultimate reward for war service -- "Learning to hate the German beast" : children as war mongers -- The hun is at the gate : protecting the innocents -- Conclusion : learning to love big brother--or not.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: World War, 1914-1918 -- Propaganda; World War, 1914-1918 -- United States; Propaganda, American; Popular culture -- United States -- History -- 20th century; World War, 1914-1918 -- Social aspects; World War, 1914-1918 -- Psychological aspects; Persuasion (Psychology); Guerre mondiale, 1914-1918 -- Propagande; Guerre mondiale, 1914-1918 -- États-Unis.; Propagande américaine.; Culture populaire -- États-Unis -- Histoire -- 20e siècle.; Guerre mondiale, 1914-1918 -- Aspect social; Guerre mondiale, 1914-1918 -- Aspect psychologique; HISTORY -- Military -- World War I; HISTORY -- Europe -- Western; Persuasion (Psychology); Popular culture; Propaganda; Propaganda, American; Psychological aspects; Social aspects; United States; 1900-1999; History